Consequences of food fussiness on nutritional status in childhood: a narrative review (Research, Society and Development, 2022)
Food fussiness is a frequent eating behavior in childhood, characterized by the triad refusal, disinterest, and resistance to food. These factors can negatively impact the intake of nutrients from the diet, contributing to changes in the nutritional status of children. Thus, this review study sought to emphasize, through a narrative literature review, the consequences of selective eating behavior on the nutritional status of healthy children by searching for original studies in the Cochrane Library, Embase, MEDLINE/PubMed, and Web of Science databases. A total of 216 studies on the subject were identified; after reading and removing duplicates, these resulted in a sample of 10 articles that comprise the present study. Through the interpretation, analysis and synthesis of the findings from the bibliographic survey, all included studies found a lower intake of fruits, vegetables, and micronutrients in selective children. Of the ten studies analyzed, seven indicated a positive association between selective eating behavior and lower weight, height, and BMI in children. Also, some barriers to be faced are the notable divergence in the methodologies used to identify and classify selectivity, and the inexistence - to date - of a universally accepted definition of classification for this eating behavior. These aspects reinforce the need for further research on the theme to enable deeper investigation and understanding of the association between the factors analyzed.